THE ROLE OF MATHEMATICAL REPRESENTATION AND DISPOSITION IN IMPROVING STUDENTS' MATHEMATICAL POWER - Imam Kusmaryono; Hardi Suyitno; Dwijanto Dwijanto (AdMathEdu : Jurnal Ilmiah Pendidikan Matematika, Ilmu Matematika dan Matematika Terapan, 2016)
The success of students in problem solving is highly dependent on the ability of students representing each developmental problems and a higher representation influenced by other representations. The aim of research to uncover and describe the capabilities and dispositions mathematical representation based on the students’ mathematical power. The subjects were students (prospective teachers of mathematics) academic year 2015/2016 Mathematics Education Department, Sultan Agung Islamic University. The numbers of students in this study were 29 students. The data collection technique using a mathematical representation tests, mathematical disposition questionnaires and interviews. The study concluded that the representation is affected by the disposition of the mathematical aspects of a person, through a positive disposition will help increase students' understanding of mathematical concepts. Furthermore, the mathematical representation will improve communication skills, perform conjecture and troubleshooting. In general disposition and mathematical representation was instrumental in enhancing the competence of the students’ mathematical power. Keywords: disposition, representations, mathematical power